Suara Perempuan di Panggung Politik: Pengungkapan Histories Profile dan Kiprah Andi Ruadah Mappiwali, 2014 - Ashari, Ashari (Rayhan Intermedia, 2025)
Women's participation in development is a role that is understood to have urgency and high selfhood. The role of women is a dignified role, a role that has symbols, which show the work of women in various roles. In this regard, this research uses the socio-historical research method. By using the sociohistories method, this study, therefore, recognises: Andi Ruaedah Mappiwali is an influential, dedicated woman from Bulukumba, who has a noble family background and extensive experience in government and organisations. Andi Ruaedah Mappiwali, has served as a member of the Bulukumba Regency DPRD and is active in various organisations, including the Golkar Party. The main spirit of entering politics is to fight for women's rights. In her view, success in development begins with people's awareness of their rights and obligations as citizens